Japan's effectiveness as a geo-economic actor navigating great-power competition - Koshino, Yuka; Ward, Robert (Adelphi series, 2022)
Yuka Koshino and Robert Ward draw on multiple disciplines--including economics, political economy, foreign policy and security policy--and interviews with key policymakers to examine Japan's geo-economic power in the context of great-power competition between the US and China. They examine Japan's previous underperformance, how Tokyo's understanding of geo-economics has evolved and, given its constitutional and other constraints on its national power-projection, what actions Japan might feasibly take to become a more effective geo-economic actor. Their conclusions will be of direct interest not only for all those concerned with Japanese grand strategy and the Asia-Pacific, but also for those middle powers seeking to navigate great-power competition in the coming decades.